Representations Of Patriarchal Cultural Responses (A Study of Content on Social Media About Sexually Suggestive Dancer) - Agung Ginanjar (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
Social media, as a digital technology product, has become a vital space in the formation and representation of culture, including patriarchal culture. Phenomena such as sexually suggestive dancers on social media platforms like TikTok, Instagram, and YouTube Shorts often spark social reactions that are steeped in patriarchal values such as moral judgment, objectification, and the reinforcement of gender stereotypes. The purpose of this study is to interpret how patriarchal culture is still reflected in social responses to sexually suggestive content on social media platforms such as TikTok, Instagram, and YouTube Shorts. The research methods used were qualitative and ethnographic approaches, with semi-structured interviews conducted with informants. The results of this study indicate that social responses are still heavily influenced by patriarchal cultural values such as objectification, moral judgment, and reinforcement of gender stereotypes against women. It can therefore be said that patriarchal culture is still very strong in the digital space and has an effect on gender inequality on social media.